2010
DOI: 10.1038/icb.2010.9
|View full text |Cite
|
Sign up to set email alerts
|

Potent anti‐tumor responses to immunization with dendritic cells loaded with tumor tissue and an NKT cell ligand

Abstract: Cancer immunotherapy is well tolerated and specific, but its efficacy remains variable. To enhance anti-tumor CD8 + T-cell responses induced by immunization with antigen-loaded dendritic cells (DCs), we explored the impact of eliciting a potent source of T-cell help from activated invariant natural killer (NK)-like T cells (iNKT cells) using the specific glycolipid ligand a-galactosylceramide (a-GalCer). As cytokines released by iNKT cells may drive proliferation of CD4 + CD25 + regulatory T cells (Tregs), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 49 publications
1
34
1
Order By: Relevance
“…Subsequently, 1x10 5 to 1x10 6 CLL cells were thawed, washed, and added back to 1x10 6 autologous B cell-depleted PBMC cultured with 1 ng/mL interleukin-7. After two further weekly stimulations, iNKT cell frequency was determined by flow cytometry.…”
Section: Autologous Response To Chronic Lymphocytic Leukemia Cells Trmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, 1x10 5 to 1x10 6 CLL cells were thawed, washed, and added back to 1x10 6 autologous B cell-depleted PBMC cultured with 1 ng/mL interleukin-7. After two further weekly stimulations, iNKT cell frequency was determined by flow cytometry.…”
Section: Autologous Response To Chronic Lymphocytic Leukemia Cells Trmentioning
confidence: 99%
“…An interferon-g enzyme-linked immunosorbent spot (ELISpot) assay was performed using a commercial kit (BD Biosciences) according to the manufacturer's instructions: 1x10 6 B-cell-depleted PBMC were washed, resuspended in complete Iscove's modified Dulbecco's medium (cIMDM) and dispensed into coated ELISpot plates. α-GalCer 200 ng/mL, phosphate-buffered saline/Tween vehicle (as a negative control), or protein phytohemagglutinin (PHA-P) 1 mg/mL (Sigma-Aldrich) (as a positive control) were added, and plates cultured for 18 h at 37°C.…”
Section: Enyzme-linked Immunosorbent Spot Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has also been reported that activated iNKT cells can unexpectedly expand Tregs (51), it is unlikely that the Glioma/Gal vaccine induced Treg activity because Treg depletion was not required for successful prophylactic vaccination. In addition, we have previously shown that an a-GalCer-pulsed dendritic cell vaccine did not alter Treg number or function (13).…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer vaccines that activate iNKT cells with a-GalCer are highly effective in animal studies, with long-lasting immunity induced in response to coadministration of tumor antigens and a-GalCer (10)(11)(12)(13). This approach has yet to be tested directly in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%